Conditional privacy preserving authentication in VANETs: a survey. (2017) - Zouaidi, Soukeina; Lengliz, Ilhem; Belghith, Abdelfettah
The trade-off between authentication and privacy is a key security aspect in vehicular ad hoc networks (VANETs). While it is necessary to authenticate and identify each communicating vehicle, it remains mandatory to insure and maintain the privacy. To this end, conditional privacy preserving authentication has been proposed. This paper surveys the existing literature on authentication schemes that conditionally thrive to protect the privacy in vehicular networks. We firstly introduce the most relevant proposed privacy preservation techniques. Then, we examine and categorise several authentication protocols based on their adopted privacy technique, pseudonyms based protocols, group signature based protocols, ring signature based protocols, blind signature based protocols, group signcryption based protocols and hybrid protocols which integrate more than one privacy preservation technique. We finally present a comparative analysis of the surveyed protocols, and identify some possible future research directions.